Plasma cells in and around the central nervous system - Merder, Alexander K.; Moseman, E. Ashley (Frontiers in Immunology, 2026)
Secreting a continuous, and sometimes life-long antibody supply, plasma cells are the effector arm of humoral immune system. With an incredibly diverse array of binding specificities, antibodies play critical roles in homeostasis and disease. Traditional views of plasma cells have them function at a distance, relying on circulation to ferry their antibodies to peripheral tissues. However, this review focuses on plasma cells that operate locally within tissues that lack ready access to circulating antibody, specifically, we explore plasma cells that accumulate within the central nervous system (CNS) and its borders. Through both antibody secretion and immunoregulation, plasma cells impact responses to neuroinvasive pathogens, CNS-targeting autoimmune diseases, and CNS tumors. In border sites, like the meninges and olfactory mucosa, plasma cells serve to protect against CNS pathogen invasion while also mediating pathology in autoimmunity and inflammatory diseases. In considering plasma cells in and around the CNS, we discuss their localization, function, migration, local differentiation, and persistence. Importantly, we examine where gaps remain in our knowledge of CNS plasma cells and how this work will impact the prevention and treatment of CNS infection and autoimmunity.